2014
DOI: 10.1128/aac.01718-13
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Vancomycin Pharmacokinetics in Neonates To Develop Practical Initial Dosing Recommendations

Abstract: f Variability in neonatal vancomycin pharmacokinetics and the lack of consensus for optimal trough concentrations in neonatal intensive care units pose challenges to dosing vancomycin in neonates. Our objective was to determine vancomycin pharmacokinetics in neonates and evaluate dosing regimens to identify whether practical initial recommendations that targeted trough concentrations most commonly used in neonatal intensive care units could be determined. Fifty neonates who received vancomycin with at least on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 47 publications
0
20
0
1
Order By: Relevance
“…Finally, a potential limitation of this study is that the achievement of steady state was not confirmed. However, paediatric drug formularies recommend determining vancomycin concentrations between 24–48 hours based on the fact that steady state is likely to have occurred …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a potential limitation of this study is that the achievement of steady state was not confirmed. However, paediatric drug formularies recommend determining vancomycin concentrations between 24–48 hours based on the fact that steady state is likely to have occurred …”
Section: Discussionmentioning
confidence: 99%
“…However, paediatric drug formularies recommend determining vancomycin concentrations between 24-48 hours based on the fact that steady state is likely to have occurred. 52,53 It is clear that individualised dosing is needed in critically ill children…”
Section: Discussionmentioning
confidence: 99%
“…18,19 For gentamicin in particular, the diversity is similar to findings in UK neonatal units. [29][30][31] An Australasian working group, including many contributors to this study, is currently formulating consensus therapeutic guidelines for vancomycin and gentamicin dosing on the dosing in children and neonates. The impact of these guidelines could be a focus in a future PPS, including collection of therapeutic drug monitoring data.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SCr ≥1.5 mg/dL persisting ≥48 h was considered an AKI 32. A SCr increase of ≥125% (≥0.15 mg/dL within a 48 h time frame) was considered a ‘potential’ AKI 33. Vancomycin-associated nephrotoxicity was defined as an event occurring between the first dose to 72 h after the last dose in a clinical episode.…”
Section: Methodsmentioning
confidence: 99%